1998
DOI: 10.1203/00006450-199803000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Apoptosis during Lung Development

Abstract: Apoptosis has been shown to be involved in several processes during embryogenesis, but the ontogeny of apoptosis during lung development ahs not been studied. The goals of the current study were to determine if apoptosis occurs during lung development, and to determine the ontogeny of the changes in apoptosis that occur. We studied the ontogeny of apoptosis in vivo using lungs from 14-18-d gestation fetal rats, newborn rats, and 1-d-, 2-d-, 5-d-, and 10-d-old rat pups. Apoptosis was assessed by electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
93
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 23 publications
11
93
4
Order By: Relevance
“…Consistent with the low apoptotic rate normally observed in postnatal lungs, 44 few positive cells were detected by terminal dUTP nick-end labeling (TUNEL) assay in the pulmonary tissue of both wild-type and Hoxa5 Ϫ/Ϫ specimens at all stages tested (not shown). Thus, apoptosis did not contribute significantly to the delayed lung growth.…”
Section: Consequences Of the Hoxa5 Mutation On Pulmonary Weight Prolmentioning
confidence: 52%
“…Consistent with the low apoptotic rate normally observed in postnatal lungs, 44 few positive cells were detected by terminal dUTP nick-end labeling (TUNEL) assay in the pulmonary tissue of both wild-type and Hoxa5 Ϫ/Ϫ specimens at all stages tested (not shown). Thus, apoptosis did not contribute significantly to the delayed lung growth.…”
Section: Consequences Of the Hoxa5 Mutation On Pulmonary Weight Prolmentioning
confidence: 52%
“…In prototypical models of apoptotic cell death, as p113 decreases due to cleavage by caspase-3, p85 increases proportionately (2). Therefore, some of the p85 content we observed is consistent with previous observations that apoptosis is part of normal development in both fetal (20) and neonatal lung (31)(32)(33). We observed that in RFL p113 content decreased significantly in late gestation, but without a proportional increase in p85 ( Figures 1A and 1B).…”
Section: Discussionsupporting
confidence: 81%
“…For the entire period, Embryonic Day 16 to adulthood, the decrease in p113 was significant (n ϭ 28, R 2 ϭ 0.27, P Ͻ 0.005). The 85-kD fragment (p85) was also detected ( Figure 1A), consistent with observations that both fetal (20) and neonatal rat lung undergo apoptosis (31)(32)(33). However, the content of p85 did not increase proportionately to the decrease in p113 in late gestation ( Figure 1B); p85 content was relatively constant prenatally (n ϭ 16, R 2 ϭ 0.003) and decreased after birth through adulthood (n ϭ 16, R 2 ϭ 0.86, P Ͻ 0.001).…”
Section: Content Of Parp-1 Protein In Fetal and Postnatal Rat Lungsupporting
confidence: 73%
See 1 more Smart Citation
“…We 10 -12 and others 13,14 have demonstrated that moderate and precisely timed alveolar epithelial type II cell apoptosis is an integral component of physiological postcanalicular lung remodeling in mice, rats, and rabbits. Although the exact biological role of apoptosis in alveologenesis remains uncertain, its choreographed occurrence across mammalian species strongly suggests apoptotic elimination of surplus type II cells during perinatal alveolar remodeling is a naturally occurring and developmentally relevant event.…”
mentioning
confidence: 99%